Maternal Knowledge of Basic Immunization Completion in Toddlers within the Buduran Primary Health Care Work Area Buduran Sub-District Sidoarjo Regency - Cahyanti, Intan Dwi; Hilmi, Muhammad Afif; Siagian, Hotmaida (Global Ten Public Health and Nursing Journal, 2024)
Basic immunization is a mandatory health program organized by the government for infants aged 0-12 months to provide immunity against preventable diseases through vaccination. The coverage of basic immunization in the Buduran Primary Health Care work area in Sukorejo Village, Buduran Sub-District, Sidoarjo Regency, still has incomplete coverage. The aim of this study is to understand the maternal knowledge regarding the completion of basic immunization in toddlers within the Buduran Primary Health Care work area, Buduran Sub-District, Sidoarjo Regency. This study utilized a descriptive method and was conducted from February to March 2023. The sample size was 50 mothers who had toddlers aged 0-12 months in Sukorejo Village, Buduran Sub-District, Sidoarjo Regency, selected through total sampling technique. The data were analyzed univariately. The results of the study showed that mothers with good knowledge who provided complete immunization accounted for 34% (17 individuals), while those with incomplete immunization accounted for 6% (3 individuals). Mothers with sufficient knowledge who provided complete immunization accounted for 6% (3 individuals), whereas those with incomplete immunization accounted for 10% (5 individuals). Mothers with poor knowledge who provided complete immunization accounted for 6% (3 individuals), whereas those with incomplete immunization accounted for 38% (19 individuals). Maternal knowledge is interconnected, contributing to the insufficient completion of basic immunization in their toddlers. Cross-tabulation was used for analysis in this scientific paper. The results of cross-tabulation indicated that the majority of mothers had poor knowledge and their children's immunization was incomplete, totaling 22 (44%). The incomplete immunization coverage among mothers with poor knowledge is attributed to factors such as a significant number of mothers having only completed high school education and lacking awareness of immunization schedules. This lack of information sources within the community necessitates greater monitoring by Posyandu cadres, motivating residents to immunize their children. Health workers are also advised to communicate immunization schedules to Posyandu cadres through their respective groups.